HUBUNGAN ANTARA KESADARAN METAKOGNISI DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA KELAS XI SMA MUHAMMADIYAH 1 KETAPANG - Mustapa Mustapa; Cawang Cawang; Mahwar Qurbaniah (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACT This study aimed at describing the students’ metacognitive awareness in Chemistry learning, at finding out the correlation of metacognitive awareness and learning outcomes, and at finding out the correlation of indicators of metacognitive awareness and learning outcomes in Chemistry subject of grade XI SMA Muhammadiyah 1 Ketapang. The subjects of this study were 32 science class students. The methodwas descriptive correlational method. The instrument was a metacognitions questionnaire (MCQ) developed by Schraw and Dennison (1994), and modified by the writer. The results showed that the students' metacognitive awareness in Chemistry was bigger than other category (43,75%). There was a positive correlation of students’ metacognitive awareness and learning outcomes by 0.933 coefficient value. The result of correlation of indicators of metacognitive awareness and student's learning outcomes indicated that the monitoring comprehension indicators contributed major influence to students’ learning outcomes by 0.894 coefficient of determination value. In conclusion, there’s significant correlation of students’ metacognitive awareness and learning outcomes by 0.933 ofcorrelation coefficient value. In addition, the dominance of students’ metacognitive awareness isat a developing stage(62,5%), and the most influential indicator is monitoring comprehension indicator (0,894).Keywords : metacognitive awareness, learning outcomes